Martin Luther King Jr., homosexuality, and the early gay rights movement keeping the dream straight? - Long, Michael G.; Tutu, Desmond 1931-2021 (Basingstoke [u.a.] Palgrave Macmillan, 2012)
Martin Luther King Jr. was neither an advocate or enemy of gay rights, but both sides of the debate use his words in their arguments. His widow cited them in her campaign for gay rights, while his daughter used them in her rejection of same-sex marriage. The author explores the legacy of Martin Luther King Jr in relation to gay rights
Introduction: Keeping the Dream Straight?. -- Part 1: Kings in conflict. "It's Consistent with His Philosophy': Coretta Scott King's Advocacy for Gay Rights ; 'He Did Not Take a Bullet for Same-Sex Unions': Bernice King's March Against Same-Sex Marriage. -- Part 2: King in context. "Your Problem Is Not At All an Uncommon One': King, Psychiatrists, and the Problem of Homosexuality ; 'I Am Fundamentally a Clergyman': King, Theologians, and the Sin of Homosexuality ; 'He Praised Him for His Ability and Contacts': King's Relationship with Bayard Rustin. -- Part 3: Civil rights and gay rights. From Black to Gay: King's Concern about Discrimination Against Gays ; From King to Kameny--and Coretta: A Final Conclusion. -- Afterword: Archbishop Desmond Tutu.
Includes bibliographical references (p. 151-186) and index
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: King, Martin Luther -- Jr -- 1929-1968 -- Political and social views; King, Martin Luther -- Jr -- 1929-1968 -- Friends and associates; King, Martin Luther 1929-1968 -- Political and social views; King, Martin Luther 1929-1968 -- Friends and associates; Gay liberation movement -- United States -- History -- 20th century; Homosexuality -- Public opinion -- History -- 21st century